2020
DOI: 10.1002/cpdd.818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxycodone Combined With Flurbiprofen Axetil on Postoperative Analgesia and Immune Function in Patients Undergoing Radical Resection of Colorectal Cancer

Abstract: The influence of surgery and anesthesia on immune function during the perioperative period should not be neglected. In this study, we evaluated the effects of oxycodone combined with flurbiprofen axetil on postoperative analgesia and immune function in patients undergoing radical resection of colorectal cancer (CRC). One hundred and thirty‐three were randomized into the oxycodone combined with flurbiprofen axetil (OF) group or the sufentanil combined with flurbiprofen axetil (SF) group. Patients in the OF grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…As a result, it has a high rate of clinical acceptance. Wan et al (2021) [ 33 ] found that oxycodone combined with flurbiprofen and axitinib for analgesia in patients with colorectal cancer could effectively reduce pain intensity, especially visceral pain, and it helped reverse immunosuppression during radical colorectal cancer resection. Li et al (2021) [ 34 ] pointed out that compared with the three-step analgesia alone, acupuncture combined with three-step analgesia could increase the reaction rate of pain relief in the treatment of cancer pain, reduce the side effects, reduce the rate of sudden pain, shorten the onset time of analgesia, and prolong the duration of the reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it has a high rate of clinical acceptance. Wan et al (2021) [ 33 ] found that oxycodone combined with flurbiprofen and axitinib for analgesia in patients with colorectal cancer could effectively reduce pain intensity, especially visceral pain, and it helped reverse immunosuppression during radical colorectal cancer resection. Li et al (2021) [ 34 ] pointed out that compared with the three-step analgesia alone, acupuncture combined with three-step analgesia could increase the reaction rate of pain relief in the treatment of cancer pain, reduce the side effects, reduce the rate of sudden pain, shorten the onset time of analgesia, and prolong the duration of the reaction.…”
Section: Discussionmentioning
confidence: 99%
“…It has a good overall effect, with a noticeable analgesic effect, low adverse effects, high patient psychological acceptance, and high satisfaction. As a result, it has a high rate of clinical acceptance Wan et al (2021) [33]. found that oxycodone combined with flurbiprofen and axitinib for analgesia in patients with colorectal cancer could effectively reduce pain intensity, especially visceral pain, and it helped reverse immunosuppression during radical colorectal cancer resection.…”
mentioning
confidence: 99%
“…Presently, numerous research groups are directing their attention towards the impact of anesthetic drugs on immune function, postoperative mortality, and recurrence rate of cancer surgery patients. [8][9][10][11][12] A comprehensive investigation of the effect of anesthetic drugs on immune function holds significant implications for perioperative medication in patients.…”
Section: Introductionmentioning
confidence: 99%